The Relationship Between Satisfaction and Travel Characteristics of International Tourists in Luang Prabang, Laos - SOUNTHALY, SengAloun; SOMSAMONE, Vilaphone; seong-il, KIM (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
This research aims to gain a better understanding of satisfaction of nature and culture-based tourist by examining their experiences. The difference between their satisfaction level and travel characteristics are needed more clarification analysis and compare. These also explore the direct impacts of the perceived experiences and individual characteristics and overall satisfaction. Such information can be very useful for planners to improve the attractiveness of the destination for the longer term. It should contribute to understand the relationships between international tourists’ characteristics, and their level of satisfaction. This can also help policymaking in formulating future strategies for tourist destination management, contributing to sustainable development, especially in Luang Prabang Province. This research has two objectives: 1) to examine the relationship between socio-demographic aspects, travel characteristics of international tourists and the categories of tourist defined based on the most popular destinations; 2) to examine whether there are differences in international tourist satisfaction levels based on different aspects of Luang Prabang tourism. The survey was conducted from April to September 2017 at three selected main points, LuangPrabang International airport; traditional-cultural tourist places; and natural tourist places. A total of 2,011 surveys were completed. This study employed descriptive statistics to analyze the demographic data. Chi-Square, t-test and one-way ANOVA were used to reveal the relationship among socio-demographic aspects of international tourists, and to examine international tourist satisfaction. The result of the study shows that there is a difference in socio-demographic aspects and travel characteristics among the three types of tourists, namely the eco-tour tourists, cultural/historic tourists, and the tourists who like to visit eco-tour and cultural sites. Furthermore, the analysis of the satisfaction level of tourists shows that the eco-tourists are highly satisfied with accommodation standard, followed by tourism attraction. The cultural tourists show high satisfaction overall in most of the aspects measured. the eco-tour cultural visitors have higher satisfaction level in tourism attraction, accommodation, public safety and security, than other tourist types.